Frequency dependence of electric field tunability in a photonic liquid crystal fiber based on gold nanoparticles-doped 6CHBT nematic liquid crystal - Chychłowski, Miłosz; Woliński, Tomasz (Photonics Letters of Poland, 2020)
In this paper, we investigate an external electric field frequency influence on a photonic liquid crystal fiber (PLCF) based on a gold nanoparticles (NPs)-doped nematic liquid crystal (LC) and its response to the external electric field. We used a 6CHBT nematic LC doped with 2-nm gold NPs in a weight concentration of 0.1%, 0.2%, 0.3%, and 0.5%. Full Text: PDF References J. C. Knight, T. A. Birks, P. St. J. Russell, and D. M. Atkin, "All-silica single-mode optical fiber with photonic crystal cladding," Opt. Lett. 21, 1547-1549 (1996) CrossRef J. C. Knight,T. A. Birks, P. S. J.Russell, , and J. P. De Sandro, "Properties of photonic crystal fiber and the effective index model", JOSA A, 15(3), 748-752, (1998) CrossRef S. A. Cerqueira,F. Luan, C. M. B. Cordeiro, A. K. George, and J. C. Knight, "Hybrid photonic crystal fiber", "Optics Express", 14(2), 926-931,(2006) CrossRef W. Bragg, "Liquid Crystals", Nature 133, 445-456, (1934) https://doi.org/10.1038/133445a0 CrossRef J. Kędzierski, K. Garbat, Z. Raszewski, M. Kojdecki, K. Kowiorski, L. Jaroszewicz, and W. Piecek, "Optical properties of a liquid crystal with small ordinary and extraordinary refractive indices and small optical anisotropy", Opto-Electronics Review, 22(3), 162-165, (2014) CrossRef Y. Li, and S. T. Wu, "Polarization independent adaptive microlens with a blue-phase liquid crystal", Optics express, 19(9), 8045-8050, (2011) CrossRef T. Woliński, S. Ertman, K. Rutkowska, D. Budaszewski, M. Sala-Tefelska, M. Chychłowski, K. Orzechowski, K. Bednarska, P. Lesiak, "Photonic Liquid Crystal Fibers - 15 years of research activities at Warsaw University of Technology", Phot. Lett. Pol., (11), (2), 22-24, (2019) https://doi.org/10.4302/plp.v11i2.907. CrossRef T.T. Larsen, A. Bjraklev, D.S. Hermann, J. Broeng, Opt. Expr. 11(20), 2589, (2003) CrossRef T.R. Woliński, K. Szaniawska, K. Bondarczuk, P. Lesiak, A.W. Domański, R. Dąbrowski, E. Nowinowski-Kruszelnicki, J. Wójcik, "Propagation properties of photonic crystal fibers filled with nematic liquid crystals", Opto-Electron. Rev. 13(2), 59 (2005) DirectLink L. Scolari, S. Gauza, H. Xianyu, L. Zhai, L. Eskildsen, T. T. Alkeskjold, S.-T. Wu, and A. Bjarklev, "Frequency tunability of solid-core photonic crystal fibers filled with nanoparticle-doped liquid crystals," Opt. Express 17(5), 3754-3764 (2009). CrossRef A. Siarkowska, M. Chychłowski, D. Budaszewski, B. Jankiewicz, B. Bartosewicz, and T. R. Woliński, "Thermo-and electro-optical properties of photonic liquid crystal fibers doped with gold nanoparticles", Beilstein Journal of Nanotechnology, 8(1), 2790-2801, (2017) CrossRef D. Budaszewski, M. Chychłowski, A. Budaszewska, B. Bartosewicz, B. Jankiewicz, and T. R. Woliński, "Enhanced efficiency of electric field tunability in photonic liquid crystal fibers doped with gold nanoparticles", Optics express, 27(10), 14260-14269, (2019) CrossRef D. Budaszewski, A. Siarkowska, M. Chychłowski, B. Jankiewicz, B. Bartosewicz, R. Dąbrowski, T. R. Woliński, "Nanoparticles-enhanced photonic liquid crystal fibers", Journal of Molecular Liquids, 267, 271-278, (2018) CrossRef